Introduction to crime, law and justice in Hong Kong - Gaylord, Mark S.; Gittings, Danny; Traver, Harold (Hong Kong University Press ; [Distributed by Eurospan], 2009)
Offers a comprehensive survey of all the major parts of Hong Kong's criminal justice system.